COVID-19 vaccines and immunization in the paediatric population - Banerjee, Indrajit; Robinson, Jared; Sathian, Brijesh (Nepal Journal of Epidemiology, 2022)
UNICEF data released thus far states that 0.4% of the deaths experienced due to COVID-19 (12300) have been recorded in those aged 20 years and below, with 58% of the deaths occurring between the ages of 10 to 19 years and 42% in those aged 0-9 years old respectively. The evidence supporting the use of immunization in the general populous stands true, however the use thereof in the paediatric population is not clear and thus the vital question which remains to be definitively answered and explored is that of vaccination in the younger paediatric age groups, namely those aged between 5 and 12 years. The deaths registered in this young populous are high and it is the duty of physicians to protect those whom are weakest through the use of the most scientifically accepted and proven methods. The national immunization programme of Nepal has a stratagem which aims to vaccinate 1.74 million children aged 12 to 17 years of age with the Moderna vaccine and plans to use the COVAX vaccine for those aged 18 years and above. The efficacy of the COVID-19 vaccines is evident and their role is vital in combatting the mortality, morbidity and development of new mutations. The role of approved vaccines such as Pfizer and Moderna in the younger age groups namely 12 to 18 years of age and 5 to 12 years of age is vital and shows a categorical increase in immunity and protection. It is thus advised for the 5- to 18-year-old cohort to receive their COVID-19 vaccinations. The efficacy of such vaccines in those aged between 6 months and 5 years is still in question and further scientific data and research will need to be undertaken so as to establish the benefits of COVID-19 immunization in the younger paediatric populous.